Lignin for energy applications – state of the art, life cycle, technoeconomic analysis and future trends. Issue 21 (13th October 2022) - Beaucamp, Anne; Muddasar, Muhammad; Amiinu, Ibrahim Saana; Moraes Leite, Marina; Culebras, Mario; Latha, Kenneth; Gutiérrez, María C.; Rodriguez-Padron, Daily; del Monte, Francisco; Kennedy, Tadhg; Ryan, Kevin M.; Luque, Rafael; et al.
Abstract : Lignin in advanced energy applications: source, extraction methodolgy, structure/property relationships. Abstract : Lignin is produced in large quantities as a by-product of the papermaking and biofuel industries. Lignin is the most abundant aromatic biopolymer on the planet with its chemical structure rendering it ideal for carbon materials production and finely tailored architectures of these sustainable carbon materials are beginning to find use in high value energy applications. This review focuses on lignin chemistry, various lignin extraction and fractionation techniques, and their impact on lignin structure/property relationships for energy applications are discussed. Chemistries behind important and emerging energy applications from recent research on this increasingly valuable sustainable polymer are described.